God Unhinged? A Critique of Quasi-Fideism - Zoheir Bagheri Noaparast (Religions)
Drawing on Wittgenstein’s On Certainty, Duncan Pritchard argues for a position he calls quasi-fideism. Quasi-Fideism is the view that hinge commitments such as “God exists” are exempt from rational scrutiny within the language game of religion. However, other religious beliefs, which are not part of the framework of hinge commitments, can be rationally assessed and evaluated. This view is to be contrasted with pure fideism, in which all aspects of religion are exempt from rational scrutiny. The success of quasi-fideism depends on demonstrating that “God exists” is, indeed, a hinge commitment. In this paper, I will review and criticize some of Pritchard’s reasons for arguing that God’s existence should be considered a hinge commitment. Additionally, I will offer reasons why “God exists” cannot be a hinge commitment. Considering the rational problem of evil, single and multiple divine attributes, and the emotional problem of evil, I will show that the non-circular rational criticism of God’s existence is possible. Following the distinction between subjective and objective certainty in Wittgenstein’s On Certainty, I will suggest that a more fruitful line of inquiry for Wittgensteinians is to examine God as a subjective certainty.